A life cycle-based investigation into the potential of a circular and low-carbon plastics economy in South Africa - Goga, Taahira (Department of Chemical Engineering, 2025)
Plastics are multi-functional materials that, while associated with numerous applications, are becoming strongly linked with the drawbacks of a primarily fossil fuel-based linear economy model. This results in the release of greenhouse gas emissions, low material recovery rates, and the environmental impacts associated with disposal and leakage. The circular economy approach is viewed as an alternative model that aims to improve environmental and economic performance, in the case of plastic systems by replacing conventional feedstock, reducing plastic litter, and creating value from waste through reuse and recovery. However, a transition from a linear to a circular model for the plastics sector remains poorly understood. Studies are generally restricted to the analysis of waste management systems with limited information available on the connection between material circularity and environmental impacts. Although several global studies have sought to explore this link using life cycle assessment methods, they do not consider national scale factors, such as the effect of a country's waste management landscape and its energy mix. This research study investigates potential future versions of a low-carbon and circular plastics economy in South Africa. The scenarios evaluated are based on local voluntary and regulatory objectives and include increased mechanical recycling, the shift from single-use consumption to reuse, and decarbonisation of the sector by integrating renewable energy into the electricity mix as well as replacement of the fossil fuel feedstock for monomer production. Furthermore, the combination of scenarios is modelled to demonstrate the potential benefit of implementing these strategies in concert. The industrial ecology tools Material Flow Analysis (MFA) and Life Cycle Assessment (LCA) are utilised to determine the degree of circularity and assess the impacts of these strategies along the plastics life cycle. The results are presented in terms of circularity and environmental indicators including but not limited to recycling rates, quantity of leakage, Global Warming Potential (GWP), and ecosystem quality. The results for the reference year (2018) demonstrate that South Africa had a per capita plastic consumption of 36 kg/capita/year, with a plastic sector input recycling rate of 40.3%, employment opportunities totalling 77 348, and a carbon footprint equivalent to 3.9% of the country's total annual emissions. Based on current practices and with no policy interventions or measures, the short-term forecast indicates that plastic production will increase by a rate of 1.7% annually between 2018 and 2025 (Baseline scenario). This will lead to a projected increase in plastic use of 1 kg/capita and a subsequent rise in leakage of 11%. Furthermore, it is expected that the degree of environmental impact will increase between 10 and 18% with a further increase of 21% in the subsequent decade. In terms of normalised results, significant impacts across all scenarios were identified as human toxicity and ecotoxicity, fossil resource scarcity, and freshwater eutrophication. Additionally, the contribution analysis revealed that the major quantifiable environmental impacts are associated with upstream processes such as monomer and polymer production and product manufacturing with a combined share of 55- 85% of the total impacts at the endpoint level (Areas of Protection). This is primarily due to coal-based pathways for feedstock and energy production. Although all the mitigation strategies, particularly elevating recycled rates, and decarbonisation of the system, display a benefit relative to the Baseline scenario, the findings demonstrate that the greatest gain amongst materiality, circularity, and environmental indicators can be achieved under the Combination scenario in 2025 with an 11.2% increase in recycled content, 1 kg/capita reduction in leakage, and an average decrease of 16% in midpoint impacts. This benefit is further extended to an additional 40.1% increase in recycled content and a 55% average improvement in environmental effects in 2035 under the medium-term forecast with levels projected to decline below historical findings for 2018. A comparison of results with global targets shows the potential of combining scenarios beyond short-term local ambitions. Notwithstanding these significant benefits in circularity and environmental impacts, leakage to the environment would still be prevalent with an estimated 256 kt of plastic debris in 2035. Despite the identification of significant potential improvements from a material and environmental perspective through the combined application of the three modelled strategies, it is concluded that these would not transform the South African plastics sector to the extent that it could be classified as fully or even largely circular nor low-carbon in the short- to medium-term. Recommendations on the material aspects include designing for recyclability, investigating the potential for chemical recycling to complement mechanical recycling, and promoting reuse business models. From an emissions perspective, the transition to renewable energy needs to be accelerated, and the introduction of lower-carbon routes for the local polymer production process should be investigated. The findings also illustrate the need for increased coordination between upstream strategies centred around design and material innovation together with downstream processes focusing on end-of-life recycling and recovery to improve the environmental profile of the South African plastics system